Expression of Vascular Endothelial Growth Factor in Nasal Polyp and Chronic Rhinosinusitis - Alireza Azizzadeh Delshad; Mohammadreza Jalali Nadoushan; Ali Davati; Aida Rostami (Iranian Society of Pathology, 2016)
Background: Nasal inflammatory disorders such as chronic rhinosinusitis and nasal polyp are among the most prevalent complications with high socioeconomic costs. Vascular Endothelial Growth Factor (VEGF) plays a key role in angiogenesis and cell proliferation. In the present study the effect of VEGF on the development and prognosis of chronic rhinosinusitis and nasal polyp was investigated. Methods: This cross sectional study was performed on the nasal histological specimens of two groups of patients suffering from nasal polyp or chronic rhinosinusitis, and the expression of VEGF in the two groups was compared immunohistochemically. Based on the percentage of VEGF-positive cells the specimens were classified into four scores. Furthermore, the relations between the VEGF expression and some demographic characteristics were evaluated. Results: The VEGF immunohistochemistry findings indicated a significantly higher expression of VEGF in nasal polyp group compared to chronic rhinosinusitis without nasal polyp group. In terms of VEGF-expression scoring, in both groups most of the specimens were classified as score-2, namely indicating 10-50% of VEGF-positive epithelial cells. In both groups no significant relation between VEGF expression and age or sex of the patients could be seen. Conclusion: Local modulation of VEGF expression might be taken as a putative therapeutic strategy in management of sinunasal inflammatory disorders, especially nasal polyps.